629=x-99

Simple and best practice solution for 629=x-99 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 629=x-99 equation:


Simplifying
629 = x + -99

Reorder the terms:
629 = -99 + x

Solving
629 = -99 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
629 + -1x = -99 + x + -1x

Combine like terms: x + -1x = 0
629 + -1x = -99 + 0
629 + -1x = -99

Add '-629' to each side of the equation.
629 + -629 + -1x = -99 + -629

Combine like terms: 629 + -629 = 0
0 + -1x = -99 + -629
-1x = -99 + -629

Combine like terms: -99 + -629 = -728
-1x = -728

Divide each side by '-1'.
x = 728

Simplifying
x = 728

See similar equations:

| 5b+6-66+2=19 | | Logx(0.546)=-1.4 | | 12x^12/4x^4 | | 28+14x=18+9x | | 4w+2w=-5-5 | | 3(6x+6)=-180 | | x=3*12+11 | | P=r(150-1.5r)-20(150-1.5r)-1500 | | =3*12+11 | | log(7)4n=0 | | 6.6x+8=4.6x+2 | | 9/4-3=9 | | -8x-9x=119 | | x-5/6-1=x-5/7 | | 19/5÷4 | | 8c+4.75=20 | | 11x+10-3x+(-7)=-9+2x | | 0.6x+14.1=x-7.3 | | 3x(4/2) | | 3(8x+9)-9x=7x+19 | | Y-0=1/4[x-(-4)] | | 14-2(3a+1)=2(3a-2) | | 7(5cx+y)=34cx-8y | | 3(4x-1.3)=5x-3.9 | | 2x^2+50x-600=0 | | 10x+2-4x-8=2x-18 | | 12(x+5)=13+2 | | -59=5+8 | | 2x^2-11=19 | | -0.9x+5.32=-0.5x+0.52 | | -9-6k=15 | | 2c^2-16c=0 |

Equations solver categories